Exploration of Entomopathogenic Nematodes in Organic Rice Field in Sleman Regency - Miftahul Ajri; Dinda Dewi Aisyah; Azizah Ridha Ulilalbab (Warmadewa University Press, 2023)
Entomopathogenic nematodes (EPNs), consisting of genera Steinernema and Heterorhabditis are biological agents proven effective in killing insect pests. Organic rice fields and sandy soil textures are potential areas for exploring the presence of EPNs. This research aims to determine the diversity of genera and populations of entomopathogenic nematodes in organic rice fields in Sleman Regency. The study was conducted on organic rice fields and the UPN